Ethics, equity and community development - Banks, Sarah ca. 20./21. Jh; Westoby, Peter ca. 20./21. Jh (Rethinking community development, 2019)
Drawing on theory and a range of cross-disciplinary and international perspectives, this book examines the place of ethics and ethical practice in community and development across a global spectrum of political, ecological and economic contexts